Young upper tract urothelial carcinoma: a case report - SA, Osama; Kamarulzaman, Mohd Nazli; MD, Mohd Ashraf; AR, Mossadeq; Rahman, Mohd Nor Gohar; Z, Mahamood; S, Hassan; Y, Maya; Zaidi, Z; Zulkarnain, H (Universiti Sains Malaysia, 2008)
Upper urinary tract transitional cell carcinomas are rare tumors. They account for 5 to 7% of the urothelial tumors with renal pelvic lesions representing the majority. The disease is rarely seen under the age of 50. Smoking, occupational carcinogens, analgesic abuse, Balkan nephropathy are the risk factors. Approximately 20 to 50% of patients with upper urinary tract transitional cell carcinomas have bladder cancer at some point on their course. We report a rare case of 20 year old man with transitional cell carcinoma of renal pelvis.